Ms Glow Strategy After PS Glow Lawsuit Regarding Trademarks - Alamsyah, Azzahra; Nurdiana, Dina; Nur Januarizky, Fira (Educationist: Journal of Educational and Cultural Studies, 2023)
The PS Glow brand bears a resemblance to the MS Glow brand name. Because the trademark owner MS Glow felt aggrieved, the trademark owner reported to the authorities on charges of using the trademark without permission. In that case, it has been proven that there is a registration without good faith carried out by PS Glow. PS Glow brand registration was made in 2021 after the MS Glow brand became known to the general public. The operation of the cosmetics factory or Skincare under the name "MS Glow" since 2016 and can be proven by the Tax Setter Letter to the Regional Revenue Service since 2018. After the lawsuit filed by PS Glow, then MS Glow needs to implement several strategies to anticipate information inequality circulating in the community. In addition, as a company that feels disadvantaged, there is also a need to prevent a continuous crisis from occurring which causes the company to be allowed to operate again.